Race for empire : Koreans as Japanese and Japanese as Americans during World War II - Fujitani, Takashi (Berkeley, CA. : University of California Press, 2011)
'Race for Empire offers a profound and challenging reinterpretation of nationalism, racism, and wartime mobilization during the Asia-Pacific war. In parallel case studies--of Japanese Americans mobilized to serve in the United States Army and of Koreans recruited or drafted into the Japanese military--T. Fujitani examines the U.S. and Japanese empires as they struggled to manage racialized populations while waging total war. Fujitani probes governmental policies and analyzes representations of these soldiers--on film, in literature, and in archival documents--to reveal how characteristics of racism, nationalism, capitalism, gender politics, and the family changed on both sides. He demonstrates that the United States and Japan became increasingly alike over the course of the war, perhaps most tellingly in their common attempts to disavow racism even as they reproduced it in new ways and forms'--
Includes bibliographical references (p. 447-468) and index.
Keywords: World War, 1939-1945 -- Participation, Japanese American; World War, 1939-1945 -- Participation, Korean; World War, 1939-1945 -- Social aspects -- United States; World War, 1939-1945 -- Social aspects -- Japan; Nationalism -- United States -- History -- 20th century; Nationalism -- Japan -- History -- 20th century; Racism -- United States -- History -- 20th century; Racism -- Japan -- History -- 20th century; Imperialism -- Japan -- History -- 20th century; Imperialism -- United States -- History -- 20th century